PENDAMPINGAN UKM WARUNG TA CAFE: PENINGKATAN MANAJEMEN USAHA DALAM MENGHADAPI PERSAINGAN - Cempaka Paramita; Fajar Destari; Kristian Suhartadi Widi Nugraha (LPPM Universitas Bina Bangsa, 2022)
The coffee shop business in Indonesia has shown significant development accompanied by intense business competition in recent years, in line with the current trend of coffee shop business that has spread nationwide, including in Jember Regency. However, since the Covid-19 pandemic era, not a few coffee shop businesses have been forced to go out of business, especially at the SME level, because they cannot manage their business properly. One of the UKM coffee shops in Jember is Warung Ta Café which has a lot of potential to be developed. However, business management or management is still not carried out professionally, so that assistance is needed through the provision of management consulting and training, especially operations / production, marketing, finance, human resources and risk management. The form of business assistance is through the provision of intensive consultation and training as well as assistance in adding several main production tools and strengthening product branding so that these SMEs can survive in the midst of competition